Perencanaan Tebal Perkerasan Kaku (Rigid Pavement) pada Jalan Kapten Piere Tendean - Dziljalal, Fadhli; Iswandi, Agung; Aida, Nur (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2023)
Jalan Captain Pierre Tendean is one of the connecting roads between Jalan Brigjend Katamso and Jalan Gatot Subroto which is often passed by local and foreign vehicles. As one of the local roads in the city of Ketapang, this road is also passed by commercial vehicles such as trucks with the heaviest axle load of 5 tons where the excessive load can trigger damage to this road, the average LHRN value on this road is 11 commercial vehicles . The existing road is still in the form of asphalt where there are several points of damage. This is one of the reasons for planning road improvement. The purpose of this study was to determine the thickness of rigid pavement, to know the plan drawings and to know the cost budget plan (RAB). From a good road there is good soil too, the soil is the basic foundation that plays an important role. One of the data needed in the planning of pavement thickness is the CBR value of the soil. The CBR value is obtained from testing with a Dynamic Cone Penetrometer (DCP), on the subgrade of this road the average CBR value reaches 8,40%. In planning the thickness of this rigid pavement using the 2017 SNI 8457 catalog as a reference that regulates the thickness of the lower foundation layer and the thickness of the concrete slab. By using the average CBR value, the thickness of the sub-base layer for this design is 150 mm, for the design lean concrete with thickness of 50 mm, 9,8 MPa or K-125 concrete is used and for the design concrete slab size is 150 mm thick, it is used. 19,3 MPa or K-225 concrete. The planned cost for the rigid pavement of Captain Pierre Tendean is Rp 518,089.000,00 (Five Hundred Eighteen Million Eighty Nine Thousand Rupiah).